2019
DOI: 10.1101/2019.12.29.882068
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Graded, multi-dimensional intragroup and intergroup variations in primary progressive aphasia and post-stroke aphasia

Abstract: Language impairments caused by stroke (post-stroke aphasia) and neurodegeneration (primary progressive aphasia) have overlapping symptomatology, nomenclature and are classically divided into categorical subtypes. Surprisingly, primary progressive aphasia (PPA) and post-stroke aphasia (PSA) have rarely been directly compared in detail. Rather previous studies have compared certain subtypes (e.g., semantic variants) or have focussed on a specific cognitive/linguistic task (e.g., reading). This study assessed a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…This suggests that classifying patients exclusively in terms of language dysfunction masks important variations in general cognitive performance in LPA. Second, when examined relative to other primary progressive aphasia syndromes in the context of language performance, LPA rarely emerges as an independent cluster, instead of mingling with other neurodegenerative disorders of language ( Sajjadi et al , 2012 ; Maruta et al , 2015 ; Hoffman et al , 2017 ; Ingram et al , 2019 ). Together, these findings suggest that the current practice of identifying LPA endophenotypes on the basis of language disturbances alone, cannot adequately capture the multidimensional nature of cognitive impairments in this syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that classifying patients exclusively in terms of language dysfunction masks important variations in general cognitive performance in LPA. Second, when examined relative to other primary progressive aphasia syndromes in the context of language performance, LPA rarely emerges as an independent cluster, instead of mingling with other neurodegenerative disorders of language ( Sajjadi et al , 2012 ; Maruta et al , 2015 ; Hoffman et al , 2017 ; Ingram et al , 2019 ). Together, these findings suggest that the current practice of identifying LPA endophenotypes on the basis of language disturbances alone, cannot adequately capture the multidimensional nature of cognitive impairments in this syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…By evaluating a large cohort of patients suffering from stroke, neurodegenerative, and post-resective aphasia, we have provided a two-dimensional framework that can visualize language impairment across a variety of disease etiologies. While the language tool assessment shared across three cohorts highlights the similarities of aphasia phenotypes across disease etiologies, as with prior dimensionality reduction studies (22), the proposed framework using only two dimensions also provides sufficient granularity to preserve clinical classifications across all cohorts. This visual method of characterizing an aphasia phenotype provides a simplified and intuitive method of rapidly assessing aphasia phenotypes across populations and time.…”
Section: Discussionmentioning
confidence: 97%
“…The behavioral similarity mirrors the neuroanatomical similarity, in which peak atrophy for patients with nfvPPA localizes to the left posterior inferior frontal gyrus and adjacent areas (3). Investigation at higher dimensions or with more detailed behavioral assessments would enable discernment of behavioral differences (22). For instance, studies of nfvPPA have shown that grammar and fluency can be dissociated; case examples of patients with nfvPPA were found to have near normal fluency but impaired grammar and vice versa.…”
Section: Interpretation Of the Two-dimension Model Across Disease Etiologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…MLSE performance may substantially aid early and accurate diagnosis. An important contribution to clinical practice is that the MLSE provides a consistent descriptive vocabulary with which clinicians can characterise patients with language disorder of any aetiology (Ingram et al ., 2020). Whilst the patients reported here were included in an MLSE validation cohort because their language disorder was clearly consistent with either the semantic, the nonfluent, or the logopenic variant of PPA, it is well known that some presentations are not easily assigned to any of these categories (‘mixed PPA’) (Grossman, 2010; Vandenberghe, 2016).…”
Section: Discussionmentioning
confidence: 99%